DEVELOPING CHANGE MANAGEMENT PROCESSES WITH SERENA DIMENSIONS CONFIGURATION MANAGEMENT SYSTEM - A Case Study in ABB Distribution Automation - Rantakari, Arto (My University, 2005)
Requirements in the software industry change and develop rapidly and there is a real need for better change management practices to achieve better quality in software products with less time and less costs. The objective of this thesis is to develop, test and implement a new change management process model and a tool for managing changes to solve the current problems in the field of the change management. Constructive and action analytical research methods are used to construct this thesis. The action analytical research method is used to define current problems in change management practices where the constructive method is based on to construct a new change management process model and a new reporting tool. During the construction a new change management process model is developed, implemented and tested in a real environment. The literature study gives a frame of reference to the theory of change management to support the construction. The result of the construction was a new way to do change management. The implementation of the new change management process model and reporting tool was successful and it solved the problems found in the case organization. The new process model proved the functionality in a real, global software project environment and was approved by the top-level management in the case organization.
Keywords: Change management; process development; software development; construction; fi=Tuotantotalous|en=Industrial Management|